KRYTYKA STANOWISKA DOKTRYNY NIEMIECKIEJ W SPRAWIE POWOJENNYCH WYWŁASZCZEŃ MAJĄTKÓW PRYWATNYCH NA ZIEMIACH ODZYSKANYCH - SOBAŃSKI, PIOTR (Wydział Prawa i Administracji UAM, 2008)
The paper focuses on the issue of transfer without compensation of ownership of private property owned by Germans living in Western Territories incorporated into Poland after WWII. The author is of an opinion that claims to that property in Germany today cannot be raised or supported. Polish ownership is effectively protected by international public law as the legal title to those transfers originated in war reparations. Chancellor G. Schroder’s statement from 2004 should be interpreted as a final waiver of claims and refusal of support of private claims. For the purpose of international law, that statement constituted a legal act. Polish property is protected by the provisions of the Convention from 1952 on the Settlement of Matters Arising out of the War and the Occupation. Those provisions were maintained in force by the so-called 2 + 4 Treaty and pursuant to them the Federal Republic of Germany shall raise no objections against reparation measures, and no claim or actions shall be admissible.
CRITICAL REMARKS ON THE STANCE OF THE GERMAN DOCTRINE ON THE REPOSSESSION OF PRIVATE PROPERTY OWNED BY GERMANS LIVING IN WESTERN TERRITORIES INCORPORATED INTO POLAND AFTER WORLD WAR II